Peremajaan Berbasis Masyarakat pada Kawasan Eks Lokalisasi Putat Jaya Surabaya - Petrus Natalivan Indradjati; Wienda Novita Sari (Diponegoro University, 2021)
The urban renewal approach is generally carried out with both physical and economic appoach. A community-based development/urban renewal approach is used for long-term results, therefore it is rarely done. Community based urban renewal study is very important because the impact is more sustainable. Urban renewal of red-light district Putat Jaya Surabaya is carried out to resolve the pressure and social economic change, which is the closing of Dolly and Jarak (Putat Jaya). The Government of Surabaya has been using a community based approach in conducting the renewal, but in doing so the Government of Surabaya has no reference, especially the know-how mechanism of a community based development. This study aims to evaluate and formulate a community-based urban renewal mechanism, so that it can be a reference in the implementation of urban renewal. The results showed that the efforts made by the Surabaya of Government had not fully met the principles of community-based urban renewal where the community had a central role in the preparation and implementation of plans and monitoring of the results of urban renewal in a participatory manner.